Evaluation of P22 Antigenic Complex for the Immuno-Diagnosis of Tuberculosis in BCG Vaccinated and Unvaccinated Goats - Arrieta-Villegas, Claudia; Infantes-Lorenzo, José Antonio; Bezos, Javier; Grasa, Miriam; Vidal, Enric; Mercader, Irene; Singh, Mahavir; Domingo, Mariano; de Juan, Lucía; Pérez de Val, Bernat (Frontiers in Veterinary Science, 2020)
Current eradication strategies of tuberculosis (TB) in goats resemble bovine TB eradication programs and mainly relay on single and comparative intradermal tuberculin tests (SITT and CITT). TB vaccination has been proposed as a cost-effective option in high prevalent herds or countries were economic compensation for slaughter positive animals is not affordable. However, TB vaccination compromises the efficiency of TB standard diagnostic tests. In this study, the performance of a new diagnostic platform, based on the P22 antigenic complex, was assessed for skin test (ST), Interferon gamma release assay (IGRA) and serology under different TB scenarios. The sensitivity (Se) of diagnostic tests was assessed in TB infected goats from the same farm (herd A, N=77) and the specificity (Sp) was assessed in two TB negative farms, one TB unvaccinated (herd B, N=77) and another vaccinated with BCG (herd C, N= 68). The single (s) P22-IGRA showed the highest Se among IGRA tests (91%) and the comparative (c) P22-ST showed the highest Sp (100% in Herd B and 98% in Herd C). Combined interpretation of techniques enabled the best diagnostic performances. Combining the CITT + sP22-IGRA improved Se (97%) compared to CITT + tuberculin-based-IGRA (95%), with a reduction of Sp (95% and 100%, respectively). In addition, combination of P22-ELISA + cP22-ST or CITT elicited similar performance in the non-vaccination context (Se: 94% and 95%; Sp: 95% and 95%, respectively) but Sp was significantly higher in the combination with cP22-ST compared to CITT in vaccination context (95% and 79%, respectively). The combination of serological tests based on P22 and MPB83 showed higher complementarity and improved 13% the Se of P22-ELISA alone. These findings suggest that either cell-mediated or antibodies based diagnostic techniques, using the P22 antigen complex, can contribute to improve the immunodiagnostic of TB in goats under different TB control strategies.